2020
DOI: 10.1177/2397847320915143
|View full text |Cite
|
Sign up to set email alerts
|

Meldonium: Pharmacological, toxicological, and analytical aspects

Abstract: Meldonium is the active molecule from Mildronate® with similar chemical structure to an amino acid, and it is known as (3-(2,2,2-trimethylhydrazine) propionate) (CAS 76144-81-5). This pharmaceutical substance is approved in Eastern Europe for cerebral and myocardial ischemia and has been on the World Doping Association’s banned substances list since January 2016. The goal of this review is to relate the use of meldonium as a doping agent, considering its pharmacological, toxicological, and analytical aspects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 65 publications
2
21
0
2
Order By: Relevance
“…PGC1-α coordinates the upregulation of mitochondrial biogenesis and plays an important role in the metabolic reprogramming in response to the dietary availability by acting as an upstream regulator of lipid and glucose oxidative metabolism in a variety of tissues [ 75 ]. It has been suggested that meldonium could be involved in the PGC1-α upregulation by acting as an inhibitor of carnitine-palmitoyltransferase-1 (CPT-1) and thus leading to the accumulation of acyl-CoA and fatty acids in the cytosol [ 21 ]. Recently, Di Cristo et al demonstrated that meldonium indeed increased PGC1-α expression on a Drosophila model of Huntington’s disease [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PGC1-α coordinates the upregulation of mitochondrial biogenesis and plays an important role in the metabolic reprogramming in response to the dietary availability by acting as an upstream regulator of lipid and glucose oxidative metabolism in a variety of tissues [ 75 ]. It has been suggested that meldonium could be involved in the PGC1-α upregulation by acting as an inhibitor of carnitine-palmitoyltransferase-1 (CPT-1) and thus leading to the accumulation of acyl-CoA and fatty acids in the cytosol [ 21 ]. Recently, Di Cristo et al demonstrated that meldonium indeed increased PGC1-α expression on a Drosophila model of Huntington’s disease [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we showed that meldonium, an anti-ischemic drug clinically used to treat myocardial and cerebral ischemia [ 18 ], also expresses strong anti-inflammatory effects in the liver [ 19 ] and renal [ 20 ] ischemia/reperfusion. By decreasing the long-chain FFAs displacement from the cytosol into mitochondria and redirecting them to peroxisomes, meldonium inhibits L-carnitine biosynthesis and transport [ 21 ]. In peroxisomes, long-chain FFAs are then, in a carnitine-independent manner, metabolized to medium- and short-chain metabolites before further oxidation in mitochondria [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that pathological acylcarnitine dysregulation in myocardial cells can be bypassed with meldonium treatment [ 70 ]. A reduction in acylcarnitine negatively affects the endoplasmic reticulum and sarcolemma, including the activity of Ca 2+ and Na + -K + ATPase [ 77 ]. Thus, meldonium is able to improve myocardial contractility, hexokinase I activity, and cellular glucose oxidation and ATP ratio through activation of AMP-activated protein kinase, an enzyme that restores ATP level [ 78 , 79 , 80 ].…”
Section: Meldonium As the Therapeutic Approach In I/r Injury-relatmentioning
confidence: 99%
“…For these reasons, we investigated the protective effect of a meldonium under the same experimental design as in the case of liver, i.e., using four-week meldonium pre-treatment in a dose of 300 mg/kg b.m./day. This dose was chosen because it is similar to the clinical human use [ 77 , 116 ] and within the range of previously studied animal doses of meldonium [ 117 ], where it proved to be both highly effective and safe.…”
Section: Meldonium As the Therapeutic Approach In I/r Injury-relatmentioning
confidence: 99%
“…Paradoxically, it appears that the same mechanism responsible for the otherwise strong anti-inflammatory effects of meldonium [ 6 , 7 ] could also be responsible for the increased mortality in sepsis. By inhibiting both the biosynthesis and transport of L-carnitine, meldonium prevents long-chain FFAs from entering mitochondria [ 8 ] and redirects them to peroxisomes instead, where they are metabolised into medium- and short-chain metabolites, some of which are further oxidised in mitochondria [ 9 ]. In this way, meldonium protects mitochondria from the accumulation of toxic long-chain FFA intermediates and reduces the risk of mitochondrial oxidative injury [ 10 ].…”
Section: Introductionmentioning
confidence: 99%